A case of severe upper alimentary tract necrosis by corrosive acid poisoning - Shaikh, Oseen; Gaur, Naveen K.; Vijaykumar, Chellappa; Kumbhar, Uday S. (International Surgery Journal, 2021)
Corrosive poisoning is common in South East Asian countries than in the West. It can be accidental or suicidal and can cause gastrointestinal tract injuries. The grade of injuries depends on several factors related to the patient and the substance causing injury. Dilemmas arise at different management levels, whether to resort to a radical surgical approach or consider more conservative approaches. We present a case of suicidal corrosive acid injury in a 23-year-old male with extensive upper gastrointestinal tract injury managed surgically. Ampullojejunostomy may be a feasible option in patients with stomach and duodenal necrosis following corrosive acid poisoning if ampulla is normal. However, its role in the emergency setting may be questionable.